Analisis Faktor Risiko Pencemaran Bahan Toksik Boraks Dan Pewarna Pada Makanan Jajanan Tradisional Yang Dijual Di Pasar-Pasar Kota Semarang Tahun 2006 - Sugiyatmi, Sri; Sulistiyani, Sulistiyani; Hanani D., Yusniar (Jurnal Kesehatan Lingkungan Indonesia, 2006)
ABSTRACT Background: The home industry of traditional food is potentially in community economic growth. However, on the other hand, it could bring on a health disorder caused by toxic material contamination such as borax and coloring agent. The aim this research is to find out risk factors that caused material toxic contamination borax and coloring agent of traditional food that be sold at traditional market in Semarang city. Methods: The research was classified as an observational research with a cross sectional approach. The  population were producer of traditional food at traditional market in Semarang City. The samples were 48 persons from eight markets. They were taken by cluster random sampling method from 47 markets in Semarang City. Data were taken based on a chemical analysis and interview method. Data analysis using cross tabulation (Chi-square test) and a multivariate analysis. Results: The bivariate analysis showed that there were significant association between the degree of education, knowledge, attitude, practice, and the toxic material borax and coloring agent contamination of traditional food that was sold at the traditional market in Semarang City. The multivariate analysis showed that OR of education (OR = 33; 95% CI 3.73-292.42), knowledge (OR = 20.7; 95% CI = 4.41 – 92.16), attitude (OR = 31; 95% CI = 6.84 – 140.46), and practice (OR = 68.2; 95% CI = 7.156 – 650.00) as  the risk factors of the toxic material borax and coloring agent contamination of traditional food that be sold at the traditional market of Semarang City. Conclusions: Education, knowledge, attitude, and practice are the risk factors of the toxic material borax and coloring agent contamination of traditional food that be sold at the traditional market of Semarang City. Keyword: risk factor; traditional food; additive material; borax; coloring agent.